Work stress and job performance in Malaysia academic sector: Role of social support as moderator - Sai, Mei Ling; Bhatti, Muhammad Awais (SCIENCEDOMAIN international, 2014)
The present study aims to investigate the relationship role conflict, job control, social support and job performance among administration staff in University Utara Malaysia (UUM),Kedah.The research was designed by using quantitative approach and survey was conducted between 6th until 17th April, 2014 in UUM.Besides, 215 questionnaires were collected to analyze the data.Results indicate that a positive and significant relationship found between job control, social support and job performance. Besides, results indicated social support moderate between role conflict and job performance showed significant relationship.Practical implication of this study able to contributes to the UUM employees to be aware of the work stress issues in their workplace and able to maintain their job performance.